Patterns of blubber fat deposition and evaluation of body condition in growing southern right whale calves (Eubalaena australis). Issue 4 (17th May 2021) - Marón, Carina F.; Lábaque, María Carla; Beltramino, Lucas; Di Martino, Matías; Alzugaray, Lucía; Ricciardi, Marcos; Fernández Ajó, Alejandro A.; Adler, Frederick R.; Seger, Jon; Sironi, Mariano; Rowntree, Victoria J.; Uhart, Marcela M.
Abstract: Marine mammals rely on blubber mainly for energy storage, buoyancy, and streamlining. Mysticetes are born with a relatively thin fat layer that grows rapidly during nursing. However, little information on blubber deposition patterns is available for baleen whale calves. We measured blubber thickness at nine body locations in 350 southern right whale ( Eubalaena australis ) newborn to 4–6‐month‐old calves that died on the Península Valdés (Argentina) calving ground from 2003 to 2019, to document changes in blubber thickness with growth. Additionally, we looked for differences in blubber thickness and lipid content of the outer/superficial blubber in calves that died in years with high (2003, 2005, 2007–2013) and low calf mortality (2004, 2006, 2014–2019) to test whether the former were suffering from gross nutritional stress. Blubber thickness increased at all body locations with calf length. Along the cranio‐caudal axis, blubber increased in the dorsal and ventral planes, but decreased laterally towards the peduncle, possibly to improve streamlining. We found no difference in blubber thickness and lipid content between high and low mortality years, suggesting that individuals were not undernourished. This is the first study to describe progressive increases in calf blubber during growth and contributes knowledge to right whale health and ontogeny.